The first five-year evaluation of cystic fibrosis neonatal screening program in São Paulo State, Brazil - Léa Maria Zanini Maciel; Patrícia Künzle Ribeiro Magalhães; Ieda Regina Lopes Del Ciampo; Maria Luísa Barato de Sousa; Maria Inez Machado Fernandes; Regina Sawamura; Roberta Rodrigues Bittar; Greice Andreotti de Molfetta; Wilson Araújo da Silva Júnior (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2020)
The Hospital of the Ribeirão Preto Medical School, University of São Paulo is one of the three screening centers in São Paulo State, Brazil, and has included a test for cystic fibrosis (CF) since February 6, 2010, by a court order. We evaluated the first five years of this CF-newborn screening program. The original immunoreactive trypsinogen (IRT)/IRT screening protocol was adopted in Brazil. A total of 173,571 newborns were screened, 1,922 (1.1%) of whom showed IRT1 ≥ 70ng/mL. Of these, 1,795 (93.4%) collected IRT2, with elevated results (IRT2 ≥ 70ng/mL) in 102 of them (5.2%). We identified a total of 26 CF cases during this period, including three CF cases that were not detected by the CF-newborn screening. The incidence of the disease among the screened babies was 1:6,675 newborns screened. Median age at the initial evaluation was 42 days, comparable to that of neonates screened with the IRT/DNA protocol. Almost all infants with CF already exhibited some manifestations of the disease during the neonatal period. The mutation most frequently detected in the CF cases was F508del. These findings suggest the early age at the beginning of treatment at our center was due to the effort of the persons involved in the program regarding an effective active search. Considering the false negative results of CF-newborn screening and the early onset of clinical manifestations of the disease in this study, pediatricians should be aware of the diagnosis of CF even in children with negative test.